Roller-Induced Bundling of Long Silver Nanowire Networks for Strong Interfacial Adhesion, Highly Flexible, Transparent Conductive Electrodes. Issue 1 (December 2017) - Chen, Yan-Ren; Hong, Chien-Chong; Liou, Tong-Miin; Hwang, Kuo; Guo, Tzung-Fang
Abstract Silver nanowires (AgNWs) have been the most promising electrode materials for fabrication of flexible transparent touch panel, displays and many other electronics because of their excellent electrical properties, cost effectiveness, synthesis scalability, and suitability for mass production. Although a few literature reports have described the use of short Ag NWs in fabrication of randomly oriented Ag NW network-based electrode, their electrical conductivities are still far lower than that of Ag films. So far, no any literature report was able to provide any simple solution to fabrication of large-area and mass-manufactural ability to address the issues, such as, conductivity, transparency, electrical current withstand, bending stability, and interfacial adhesion. In the current work, we provide a simple solution to conquer the above-mentioned challenges, and report the development of long Ag NW bundle network electrodes on large area PET films that were coated, aligned, and bundled quickly and simply using a steel roller. Our developed AgNWs-bundle networks had superior performance in optoelectronic properties (sheet resistance 5.8 Ω sq−1 ; optical transmittance 89% at 550 nm wavelength), electrical current withstand up to 500 mA, and bending stability over 5000 bending cycles, and strong interfacial adhesion.